Morphophysiological dormancy in the basal angiosperm order Nymphaeales - Dalziell, Emma; Baskin, C.; Baskin, J.; Young, R.; Dixon, Kingsley; Merritt, D. (Oxford University Press, 2019)
Background and Aims: Substantial evidence supports the hypothesis that morphophysiological dormancy (MPD) is the basal kind of seed dormancy in the angiosperms. However, only physiological dormancy (PD) is reported in seeds of the ANA-grade genus Nymphaea. The primary aim of this study was to determine the kind of dormancy in seeds of six species of Nymphaea from the wet-dry tropics of Australia. Methods: The effects of temperature, light and germination stimulants on germination were tested on multiple collections of seeds of N. immutabilis, N. lukei, N. macrosperma, N. ondinea, N. pubescens and N. violacea. Embryo growth prior to hypocotyl emergence was monitored. Key Results: Germination was generally <10 % after 28 d in control treatments. Germination percentage was highest at 30 or 35 °C for seeds exposed to light and treated with ethylene or in anoxic conditions in sealed vials of water, and it differed significantly between collections of N. lukei, N. macrosperma and N. violacea. Seeds of N. pubescens did not germinate under any of the conditions. Embryo growth (8-37 % in length) occurred before hypocotyl emergence (germination) in seeds of the five species that germinated. Conclusions: Fresh seeds were dormant, and the amount of pregermination embryo growth in seeds of N. lukei and N. immutabilis was relatively small, while in seeds of N. macrosperma, N. ondinea and N. violacea it was relatively large. Thus, seeds of N. lukei and N. immutabilis had PD and those of N. macrosperma, N. ondinea and N. violacea had MPD. Overall, we found that seeds in the most phylogenetically derived clades within Nymphaea have MPD, suggesting that PD is the most likely basal trait within the Nymphaeales. This study also highlights the broad range of dormancy types and germination strategies in the ANA-grade angiosperms.